Armigatus felixi sp. nov. An Albian double armored herring (Clupeomorpha, Ellimmichthyiformes) from the Tlayúa lagerstätte, Mexico. (October 2022) - Than-Marchese, Bruno Andrés; Alvarado-Ortega, Jesús
Abstract: Armigatus felixi sp. nov. is described and named here based on three almost complete specimens from the shallow marine Albian deposits of the Tlayúa Quarry, near Tepexi de Rodríguez, Puebla, Mexico. This second species of Armigatus from America shows the features of the superorder Clupeomorpha and order Ellimmichthyiformes, a series of abdominal scutes as well as the mesoparietal condition and a series of predorsal scutes lateroposteriorly expanded, respectively. Also, this species shows the most outstanding feature of Armigatus, its predorsal scute series is incomplete, which was previously considered as diagnostic and now is present at least other three of its nominal species. In the new species and A. carrenoae show the last predorsal scutes exhibit a subtriangular shape in which a middle spine is protruding backward. Additionally, the new species differs from other nominal specie of Armigatus because its pelvic fin opposes the last part of the predorsal region of the trunk, and its anal and dorsal fins distinctively have 21 and 14 rays respectively. A phylogenetic study suggests that Armigatus is a paraphyletic genus, and its seven nominal species are scattered into the family Armigatidae. In this hypothesis, the Mexican Albian species, A . felixi sp. nov. and A. carrenoae are sister species separated from the Cenomanian Lebanese species, A. alticorpus and A. brevissimus that also are sister species. These last four species noticeably share a peculiar set of characters, as the incomplete predorsal scutes series, a relative low number of predorsal scutes (8–9), and the presence of the osteoglossid tooth patch in the parasphenoid, which reveal that these might be more close related. In the other nominal species of Armigatus, A. dalmaticus, A . namourensis, and probably A. oligodentatus, the predorsal scutes series is complete as in the other ellimmichthyiforms, supporting the idea that these must be allocated in another genus; however, the morphology and relationships of Mexican and Lebanese species deserve an accurate study that goes beyond the present study; therefore, for the moment no nominal species of Armigatus is taxonomically reassigned. Highlights: Armigatus felixi sp. nov is reported here as second American species of the genus from Albian Tlayúa quarry. Information is provided on the variation of shape and coverage in predorsal scutes series into Armigatus. Phylogenetic analyses show that the two Albian Armigatus are close each to other while rest species are separated, thus the genus is proposed as paraphyletic taxa.